Command failure in war : psychology and leadership - Pois, Robert A. (Indiana University Press, 2004)
Command Failure in War looks at the failures of seven military leaders, detailing not only the strategies-gone-awry, but also delving into the psyches of those who devised them. The authors consider the causes and consequences of decision-making in war through these notable defeats: Frederick the Great at Kunersdorf; Napoleon in Russia; the Civil War campaigns of McClellan, Lee, and Hood; the British military in World War I; Winston Churchill's strategic bombing; and Hitler at Stalingrad.